2022
DOI: 10.2147/jmdh.s361305
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of the Capacity-Motivation-Opportunity Pharmacist-Led Intervention in People Living with HIV in Spain, 2019–2020

Abstract: Background People living with HIV (PLWH) have significantly enhanced their life expectancy. Consequently, age-associated comorbidities and related health conditions are increasingly found in PLWH complicating their clinical management. Objective To determine the effect of the capacity-motivation-opportunity (CMO) structured pharmaceutical care intervention for improving clinical health-care results frequently associated to PLWH. Methods Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“… 8 CMO model reduces the cardiovascular risk, 19 and it has been recently shown to improve biochemical parameters, such as cholesterol, triglycerides, HDL and blood pressure. 16 We found that cardiovascular variables remained unchanged, except for blood pressure and HbA1c. In the traditional group, end-of-treatment blood pressure was more likely to be middle to high.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“… 8 CMO model reduces the cardiovascular risk, 19 and it has been recently shown to improve biochemical parameters, such as cholesterol, triglycerides, HDL and blood pressure. 16 We found that cardiovascular variables remained unchanged, except for blood pressure and HbA1c. In the traditional group, end-of-treatment blood pressure was more likely to be middle to high.…”
Section: Discussionmentioning
confidence: 58%
“…12 However, in 2017, a new model based on Capacity-Motivation-Opportunity (CMO) pillars changed this paradigm, strengthening the idea that the patient and their circumstances, in terms of complexity, adherence or polypharmacy, needed to be at the centre of the model and managed according to a multidisciplinary and multidimensional perspective. 13,14 To test this new model, patient activation, 15,16 adherence to ART, 17,18 adherence to concomitant medication, 15,18 clinical outcomes 16,17,19 and patient experience 20 were assessed in PLWH treated using the CMO model. Studies showed that this approach positively influenced these variables, and that both patients and healthcare professionals generally agreed on the benefit of the pharmacy intervention.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations